2016
DOI: 10.1590/0102-311x00038715
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the value of generic drugs in São Paulo, Brazil

Abstract: The objective of this study was to assess the perceptions of opinion-leaders, patients and their accompanying family members or carers about generic drugs. Three groups of participants were surveyed: (i) 50 customers while they were visiting commercial pharmacies located in São Paulo city, Brazil, (ii) 25 patients and 25 companions while they were waiting at the university outpatient clinic, and (iii) 50 healthcare opinion-leaders from government, hospitals, health plans, academia, and pharmaceutical companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(24 reference statements)
0
4
0
2
Order By: Relevance
“…Factors related to the behavior of consumers, prices, or even the suggestions of clerks may be influencing this choice. A study conducted in Brazil has shown differences on the perceptions regarding generic drugs 28 . Nardi et al 28 have pointed out price, effectiveness, and safety as important factors that may contribute to the decision to purchase generic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Factors related to the behavior of consumers, prices, or even the suggestions of clerks may be influencing this choice. A study conducted in Brazil has shown differences on the perceptions regarding generic drugs 28 . Nardi et al 28 have pointed out price, effectiveness, and safety as important factors that may contribute to the decision to purchase generic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the changes in the environment, the relevance of this study also finds support in the insufficiency of studies on the subject. Although this problem has been studied in IJPHM 11,4 several countries (Decollogny et al, 2011;Dunne et al, 2014;Frisk et al, 2011;Kjoenniksen et al, 2006;Kobayashi et al, 2011;Nardi and Ferraz, 2016;Rathe et al, 2013;Rozano Suplet et al, 2009), previous research is either too descriptive, lacking the explanatory power or do not take a consumer behaviour perspective. Moreover, regarding the Portuguese reality, there are few studies (Dylst, 2012;Quintal and Mendes, 2012;Simoens, 2009;Vogler, 2012) that look at the choice process of mandatory prescribed drugs, and all of them prior to the most recent legislation change, with the exception of Duque et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…É importante ressaltar que estes são submetidos aos testes de avaliação que podem garantir a eficácia de ambos, o que favorece a satisfação e confiança na população. Nardi & Ferraz (2016) observaram que a maioria das pessoas entrevistadas acreditam que os medicamentos genéricos e o medicamento de marca foram igualmente eficazes (66%), e que os medicamentos genéricos causam o mesmo efeito que o de marca (90%) (28) , o que corrobora para um melhor aceitação dos medicamentos genéricos por parte da população usuária de medicamentos, em comparação aos de referência, confiança esta que tem crescido a cada dia.…”
Section: ___________________________________________________________________________unclassified